1991
DOI: 10.1126/science.1718039
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nucleosomal Cores and Histone H1 in Regulation of Transcription by RNA Polymerase II

Abstract: The relation between chromatin structure and transcriptional activity was examined by in vitro transcription analysis of chromatin reconstituted in the absence or presence of histone H1. To maintain well-defined template DNA, purified components were used in the reconstitution of chromatin. Reconstitution of nucleosomal cores to an average density of 1 nucleosome per 200 base pairs of DNA resulted in a mild reduction of basal RNA polymerase II transcription to 25 to 50 percent of that obtained with naked DNA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
233
1
4

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(249 citation statements)
references
References 64 publications
11
233
1
4
Order By: Relevance
“…How the presence of nucleosomes on chromatin allows its replication and transcription to take place is an important and interesting question. Although both the status of nucleosomes and the role of histones in transcription initiation are becoming more and more clear (Grunstein, 1990b;Laybourn & Kadonaga, 1991;Workman et al, 1991), the status of nucleosomes during transcription elongation remains controversial (Lorch et al, 1988;Grunstein, 1990b;Clark & Felsenfeld, 1991 ;Kornberg & Lorch, 1991;Lee & Garrard, 1991;Thoma, 1991;Felsenfeld, 1992). The answer to this question spans two extremes: nucleosomes either dismantle or remain intact.…”
Section: ~~mentioning
confidence: 99%
“…How the presence of nucleosomes on chromatin allows its replication and transcription to take place is an important and interesting question. Although both the status of nucleosomes and the role of histones in transcription initiation are becoming more and more clear (Grunstein, 1990b;Laybourn & Kadonaga, 1991;Workman et al, 1991), the status of nucleosomes during transcription elongation remains controversial (Lorch et al, 1988;Grunstein, 1990b;Clark & Felsenfeld, 1991 ;Kornberg & Lorch, 1991;Lee & Garrard, 1991;Thoma, 1991;Felsenfeld, 1992). The answer to this question spans two extremes: nucleosomes either dismantle or remain intact.…”
Section: ~~mentioning
confidence: 99%
“…A growing body of evidence from both in vivo and in vitro studies has shown that the structure of chromatin influences gene expression (see references 25 and 53 for reviews). Biochemical experiments have shown that histones can repress transcription in vitro (see reference 53 for a review) and that transcriptional activators can overcome this repression (21,41,45,79,81,82). In vivo experiments in Saccharomyces cerevisiae have shown that the loss of transcriptional activators or of activator binding sites can be suppressed by mutations in histone genes (27,30,37,57).…”
mentioning
confidence: 99%
“…Prior to 2001, histone H1 had only been incorporated into chromatin using salt dialysis (14) or S-190 cell extracts from Drosophila (6). While these methods are still widely used today, we feel it is best to take advantage of a recombinant system for assembling chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the core histone to DNA ratio at which templates are best assembled in the presence of linker histone should be less than the ratio from chromatin assembled in the absence of H1. Topological analysis can be used as indirect assay for incorporation of H1, as binding of the linker histone increases the DNA associated with each nucleosome (14,15).…”
Section: Chromatin Assembly and Quality Control H1-chromatin Templatementioning
confidence: 99%
See 1 more Smart Citation